IMPLEMENTASI PENGGUNAAN MEDIA DIGITAL BAGI PERTUMBUHAN JEMAAT BERDASARKAN 1 KORINTUS 9:20-21 DAN IMPIKASINYA BAGI JEMAAT GEREJA PANTEKOSTA ISA ALMASIH HOFALO MALANG - Estin Lorenza Halawa; Sozanolo Telaumbanua (Alucio Dei, 2022)
Survey on the use of digital media for congregational growth at the Pentecostal Church of Isa Almasih Hofalo Malang. From the results of the discussion, it was found that digital media can be used as a medium for preaching (the gospel), as well as helping the growth of the congregation in terms of recognizing the truth of God's word. And this digital media is very influential for the growth of the congregation, precisely at the Isa Almasih Hofalo Pentecostal Church, Malang. This is done with the aim of knowing how the influence of digital media for the growth of the congregation at the Pentecostal Church of Isa Almasih Hofalo Malang, so that the use of media can have an impact and bring blessings in their introduction to the truth of God's word. The research method used in writing this thesis is to use quantitative methods. And to carry out the research method, the things that will be done are: first, data collection and collection through journals and books related to the titles discussed in this thesis. Second, by distributing a questionnaire (questionnaire) to the congregation of the Pentecostal Church of Isa Almasih Malang. The total population used is 32 respondents. Before the question instrument is used, to obtain good data, validity testing and reliability testing are first carried out. The data analysis technique used is descriptive data, normality test and simple linear regression test. Based on the results of research and calculations carried out using the SPSS 16.0 program as shown in the Coeffients table, the variable using digital media has a significance value of 0.000. The results in this study obtained a significance value of 0.000 < 0.05, it can be concluded that the hypothesis which reads "there is an effect of using digital media for the growth of the Isa Almasih Hofalo Pentecostal Church congregation in Malang" is accepted.